Preventing Disruptive Behavior in Elementary School Students: An Academic Investigation from a Multicultural Islamic Education Lens - Khoirotun, Ulfun; el yunusi, Muhammad Yusron Maulana (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
The objective of this study is to identify strategies for enhancing the social development of children within inclusive educational settings. The present study employs a qualitative research design and adopts a phenomenological framework. The study was conducted in SD Muhammadiyah 3, Ikrom Wage Sidoarjo, with a sample size of five individuals who were chosen as participants. The data collection process involved the utilisation of in-depth interviews and observation techniques, which were subsequently followed by data reduction and data display procedures. Subsequently, the data underwent analysis by the method of triangulation. The present study yielded the subsequent findings: The term